(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Christopher Hampton, Trevor Griffiths, and David Hare have dealt with the colonizer- and-colonized equation through English narratives, permeated with what might be termed as post-colonialist discourse. Their plays, focused on in this paper, have tackled Arabic themes and images, in varied ways, setting contrasts between two cultural Identities: the Arab, Islamic and Third World versus the Western, Judo-Christian and Developed World. Each writer has shed light on the post-colonial status of three parts of the Arab World. In Hampton’s White Chameleon Egypt emerged as a tolerant country of versatile story tellers, Griffths’ The Gulf between Us depicts –symbolic- Iraq as a cradle of civilization devastated by Western military technology, and finally Hare’s Via Dolorosa portrays Palestine as a land claimed by two communities, whereby Hare gives prominence to the Palestinian narrative. عالج كلٌ من كريستوفر هامبتون، وتريفور جريفيث، وديفيد هير معادلة المستعمِر/المُستَعمَر من خلال نصوص إنكليزية، حافلة بما يمكن تسميته خطاب ما بعد-الاستعمار. تناولت مسرحيّاتهم، التي درست في هذه الورقة، موضوعات وصوراً عربيّة، بأساليب عدَة، حيث وردت مفارقات بين هويّتين ثقافيّتين: العالم الثالث العربي الإسلامي في مواجهة العالم الغربي المسيحي- اليهودي المتطوّر. كما لجأ كلّ كاتب منهم إلى مجموعة من السمات الثقافية في عرض حالة ما بعد-الاستعمار. فبرزت مصر في مسرحية ((الحرباء الأبيض)) لهامبتون بلداً متسامحاً حافلاً برواة حكّائيين متعددي الأوجه، وصوَرت مسرحية جريفيز ((الخليج بيننا)) العراق –المرمّز – مهداَ للحضارات التي دمّرتها التقانة العسكريّة الغربيّة، وفي خاتمة المطاف أظهرت مسرحية هير ((درب الآلام)) فلسطين أرضاَ تتنازعها جماعتان من البشر، حيث يضع هير سرديّة الفلسطينيّين في الصدارة.